2008
DOI: 10.1021/ma8011569
|View full text |Cite
|
Sign up to set email alerts
|

Unique Thermal Conductivity Behavior of Single-Walled Carbon Nanotube−Polystyrene Composites

Abstract: Introduction. Carbon nanotubes have extremely high thermal conductivities; single-walled carbon nanotubes (SWCNTs) have been predicted through molecular dynamics modeling to have a thermal conductivity up to 6600 W/(m K). 1 This value is more than 10 times the value for copper and 2 times more than the highest thermally conductive diamond. An obvious SWCNT application would therefore be a high thermally conductive dispersion for applications such as heat conducting composites 1 or heat transfer fluid suspensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 19 publications
4
65
1
Order By: Relevance
“…The T g of the PS and composites studied here was 376 K, as determined by differential scanning calorimetry ͑DSC; TA Instruments Q200͒. However, in contrast to the earlier study using a modulated DSC technique, 28 we found that most samples exhibited an irreversible drop in above T g ͑one exhibited no change͒.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…The T g of the PS and composites studied here was 376 K, as determined by differential scanning calorimetry ͑DSC; TA Instruments Q200͒. However, in contrast to the earlier study using a modulated DSC technique, 28 we found that most samples exhibited an irreversible drop in above T g ͑one exhibited no change͒.…”
contrasting
confidence: 63%
“…A recent study of SWCNT/PS composites by Peters et al 28 suggested that a change in interfacial thermal resistance also should occur at the glass transition temperature ͑T g ͒. The T g of the PS and composites studied here was 376 K, as determined by differential scanning calorimetry ͑DSC; TA Instruments Q200͒.…”
mentioning
confidence: 72%
“…This is an interesting result that needs to be validated with experimental measurements. Very recent results by Peters et al [21] indicate that the thermal conductivity of SWNTpolystyrene composites does not increase with the volume fraction of the CNTs as much as one would predict. The reason might very well be the increase of the SWNT-SWNT contact points in the composite, or the value of the thermal boundary resistance.…”
Section: Effects Of Inter-cnt Contactmentioning
confidence: 87%
“…In this case, 5 wt% SWCNTs caused a 30% decrease of the heat capacity. Moreover, one DSC study indicates a similar decrease for polystyrene with 5 wt% SWCNTs [40], but another reports essentially no change for a 2.5 wt% SWCNT/polystyrene composite [41]. A DSC study of 1 wt% SWCNTs in poly(methylmethacrylate) [42] also shows essentially the same heat capacity as the neat polymer.…”
Section: Heat Capacity Of Nylon-6 and Mwcnt/nylon-6 Compositementioning
confidence: 97%